Principles of Religious Flexibility in Performing Prayers during the Covid-19 Crisis - Benseng, Abdulroya (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
The Covid-19 pandemic has unavoidably affected people’s ways of life, not only changing their daily routine, but also the ways they perform religious duties, specifically performing obligatory prayers and congregational prayers (Friday prayers). As the prayers are the second of the five pillars in Islam, it is obligatory for every Muslim man to perform the prayers collectively (known as Jama'ah) at mosque. However, Islam embodies flexibility that allows the Muslim men to either practice social distancing during the prayers at mosque or permit them to perform the prayers at home in specific circumstances such as the Covid-19 crisis. This flexibility leads to amendment to Islamic call to prayers from the usual 'hayya alas-salah' or 'come to prayer' to 'al-salatu fi buyutikum' or 'pray in your homes'. Some Islamic scholars viewed this amendment as Sunnah or 'the practices of the prophet Muhammad'. However, some viewed this as Wajib or 'obligatory'. There are two perspectives of Islamic scholars on the Jama'ah and the Friday prayers in this circumstance. First, some scholars perceived that, according to Al-Quran and Al-Hadith, both prayers are obligatory. Second, based on some other scholars’ perspectives, while the Jama'ah prayers are Al-Wajib al-Kifa'I (collective obligation), which means Nadab (recommendation), the Friday prayers are not obligatory in this circumstance for their safety and convenience. This should be taken into consideration in order to protect lives from the Covid-19 pandemic.